Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor pada Samsat Kota Padang - R Rahmawati (Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine taxpayer compliance in paying motorized vehicle taxes at the Padang City Samsat as an Intervening Variable: Public Awareness, Tax Sanctions, and Service Quality, the population in this study found 400 people with a sample of 400 respondents. The data was obtained by conducting a questionnaire, then processed and tested using SPSS. From the research conducted, it is known that based on the results of hypothesis testing, it shows that the test results show that awareness, sanctions and service quality have a significant effect on taxpayer compliance.